2011
DOI: 10.30843/nzpp.2011.64.6012
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and crop selectivity of saflufenacil alone and with partner herbicides for weed control in maize

Abstract: The recently developed herbicide saflufenacil was evaluated in six field trials between 2008 and 2011 for weed control in maize (Zea mays) crops Trial sites varied considerably in soil characteristics and weed spectrum No phytotoxicity or visual damage symptoms were observed in any of the six cultivars planted When used alone at 70 or 105 g ai/ha saflufenacil provided effective control of annual broadleaf weeds including atrazine and dicambaresistant fathen (Chenopodium album) but had little activity on grass … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 8 publications
0
8
0
1
Order By: Relevance
“…Saflufenacil can be used as a PP herbicide or desiccant for soybean in eastern Canada (Anonymous 2014). GR Canada fleabane and other herbicide resistant weeds, such as ALS resistant prickly lettuce (Lactuca serriola L.), can be controlled by saflufenacil (Liebl et al 2008;Soltani et al 2010;Trolove et al 2011); however, control of specific broadleaf weeds depends on application rate (Geier et al 2009;Soltani et al 2012). Furthermore, Mellendorf et al (2013) found that the control of GR Canada fleabane increased as the rate of saflufenacil increased from 25 to 50 g a.i.…”
Section: Introductionmentioning
confidence: 99%
“…Saflufenacil can be used as a PP herbicide or desiccant for soybean in eastern Canada (Anonymous 2014). GR Canada fleabane and other herbicide resistant weeds, such as ALS resistant prickly lettuce (Lactuca serriola L.), can be controlled by saflufenacil (Liebl et al 2008;Soltani et al 2010;Trolove et al 2011); however, control of specific broadleaf weeds depends on application rate (Geier et al 2009;Soltani et al 2012). Furthermore, Mellendorf et al (2013) found that the control of GR Canada fleabane increased as the rate of saflufenacil increased from 25 to 50 g a.i.…”
Section: Introductionmentioning
confidence: 99%
“…Two herbicides, saflufenacil and topramezone, were recently registered for weed control in New Zealand maize and sweet corn crops. Saflufenacil applied pre-emergence, in combination with acetochlor, provides good control of annual grass and broadleaf weeds (Trolove et al 2011), while topramezone, tank mixed with atrazine, has shown good efficacy on a mixed spectrum of annual broadleaf and grass weeds when applied post-emergence to maize crops (Rahman et al 2013). Saflufenacil is a new herbicide of the pyrimidinedione chemical class that acts by inhibiting the enzyme protoporphyrinogen IX oxidase (PPO) which in turn prevents chlorophyll biosynthesis (Grossmann et al 2010).…”
Section: Introductionmentioning
confidence: 99%
“…It can control more than 70 kinds of broadleaf weeds including troublesome and herbicide‐resistant broadleaf weeds, such as horseweed ( Conyza canadensis [L.] Cronq.) , giant ragweed ( Ambrosia trifida L.) in corn, soybean, and other crops when used alone or with other partner herbicides . Differently from glyphosate, saflufenacil is a selective herbicide, and the selectivity is based on physical placement and rapid metabolism in tolerant crop species .…”
Section: Introductionmentioning
confidence: 99%